Preventing The Climate Crisis: Testing Our Commitments - Paskal Kleden (Masyarakat Indonesia, 2010)
Al Gore received a degree in government from Harvard University in 1969. Afterwards, he worked as a congressman and as a senator. In 1993 Gore was elected as the 45th vice president of the United States, and served for eight years. On top of all that, he and the Intergovernmental Panel on Climate Change (IPCC) were jointly awarded the Nobel Peace Price in 2007. That is quite a CV.In Our Choice he powerfully argues that we have all the required technologies to prevent climate change. The only thing that is lacking is political will. The chapters of this book demonstrate Gores technical understanding of the climate crisis. His explanations cover energy sources, living systems, ways to use energy efficiently, the obstacles we need to overcome, and a solution of how to effectively address the crisis. Shortly said, the readers of this book will be fascinated by Al Gores knowledge in biology, engineering, economics, demography and of course politics.One aspect that might not commonly be mentioned in a scientific review but I believe is unique of this book is the format. The book combines text - book style presentations of data with textual explanations of complex phenomena. It also includes hundreds of photographs with the quality rivaling that of the National Geographic.